Porcine reproductive and respiratory syndrome: characteristic features of the infected fetus - Raymond R Rowland R; Jerome C Nietfeld; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Pregnant gilts were infected at 90 days of gestation with porcine reproductive and respiratory virus (PRRSV) isolate SD-23983. Fetuses recovered between 109 and 112 days of gestation were analyzed for the presence of PRRSV. The results showed that not all fetuses were infected, and that infected fetuses tended to be clustered within the uterine horns, suggesting that virus is spread from fetus to fetus. Even though affected litters exhibited different degrees of gross pathology, the presence of an anatomical abnormality was not an identifier of an infected fetus. Analysis of virus replication in individual tissues identified the thymus as the principal site of PRRSV replication. The results show that PRRSV infection in the developing fetus follows a unique course and that PRRSVinduced alterations may be the result of the effect of PRRSV on maternal tissues. These factors need to be taken into consideration when diagnosing PRRSV infection as the cause for aborted and stillborn fetuses.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Porcine Reproductive and Respiratory Syndrome Virus; PRRS; Diagnostics; Fetal infection; Swine